Guidewire simulation of endovascular intervention: A systematic review. Issue 6 (19th August 2022) - Qiu, Jianpeng; Ming, Jianzhong; Qian, Cheng; Chen, Yang; Gao, Dazhi; Zhou, Shoujun; zhao, Gang; Tang, Shujun; Xing, Liudong
Abstract: Background: Endovascular intervention is an important minimally invasive surgery that requires professional skills to operate surgical instruments. Such skills are mainly gained through the traditional training paradigm of "see one, do one, teach one", rather than the guidewire simulation system. Methods: To identify limitations of existing guidewire simulation research and suggest further research orientations, a comprehensive search on literature published from 2007 to 2021 is performed in 11 selected electronic databases. Through our scrutiny and filtration, 34 articles are selected as major studies for careful examinations. Results: We identify challenges faced in the field of endovascular intervention guidewire simulation. We examine and classify guidewire simulation techniques (including guidewire models, collision detection methods and collision response methods), accuracy evaluation methods, error sources, and performance optimization methods. Conclusions: Guidewire simulation can satisfy the urgent need to train surgeons, thus more efforts should be dedicated enabling its wide application in clinical environment.